Study on Sesquioxide Content and Lime Requirement of Lateritic Soils - Singh, T. Basanta; Patra, S. K.; Devi, K. Nandini (International Journal of Bio-resource and Stress Management, 2023)
Laterite and lateritic soils of Andhra Pradesh are of found in patches. They were red to dark brown, sandy clay loam to clay, moderately acidic to neutral in reaction, non saline and high in sesquioxide (R2O3) contents. The soils of the study area except for Krishnapur series (Inceptisol) were Alfisols, interpreted by presence of illuvial-B horizons with higher base saturation. The sesquioxide content ranged from 13.77 to 30.06% in profiles and from 15.23 to 28.53% in surface samples. The lime requirement (LR) ranged from 1.7 to 3.1 t ha-1 in profile samples and from 1.2 to 6.4 t ha-1 of CaCO3 in surface samples. There was a decrease in sesquioxide contents in most of the profiles and decrease in LR with increasing depth in some profiles. Lower pH directed towards higher LR. With the increase in clay content there was increase in LR in surface soil but trend did not followed with profile soils. Sesquioxide was not correlated significantly with LR. The DTPA extractable micronutrients like Zn, Fe, Cu and Mn content of profile samples ranged widely from 0.121-2.120, 4.77- 41.78, 0.459-6.256 and 8.28-80.00 ppm respectively and 0.532-3.228, 12.00-75.46, 1.336-11.502 & 52.78-81.98 ppm respectively for surface samples. Significant positive correlation existed between DTPA extractable Fe and Mn with sesquioxides in top soils but not with profile soils.